(untitled) (Bangladesh Journal of Agricultural Research, 2022)
Field experiments on broccoli cv. ‘BARI Broccoli-1’ was carried out during two consecutive rabi seasons of 2014-15 and 2015-16 at the field of Plant Physiology Section of HRC, BARI. 30 days old seedlings were treated before transplanting by dipping their roots for 24 h in different concentrations of GA3 (Gibberellic acid) viz., 20, 40, 60, 80 and 100 ppm along with control (distilled water). The experiment was laid out in a Randomized complete block Design with three replications. GA3 concentrations significantly influenced the growth parameters, yield and yield attributes and quality parameters of broccoli. In regard to the average data of two years, GA3 @ 60 ppm gave the maximum leaf length (46.58 cm), spread diameter (52.38 cm), head circumference (38.2cm cm), head length (16.60 cm), head diameter (15.45 cm), primary and secondary head weight/plant (289.85 g and 192.80 g). The maximum head yield (18.82 t/ha in 2014-15 and 21.39 t/ha in 2015-16) with an average of 20.11 t/ha was recorded at GA3 @ 60 ppm followed by GA3 @ 40 ppm. Application of GA3 @ 60 ppm also produced the highest head compactness index (18.77 g/cm), maximum vitamin C (82.88 mg/100 g FW), vitamin A (601.90 IU/100 g FW) contents and the highest total soluble solid (10.10%). From the investigation it was also observed that application of more than 60 ppm GA3 reduced the yield attributes and yield of broccoli. Bangladesh J. Agril. Res. 45(3): 247-259, September 2020